1984
DOI: 10.1159/000183321
|View full text |Cite
|
Sign up to set email alerts
|

Trace Element Concentrations in Hair, Fingernails and Plasma of Patients with Chronic Renal Failure on Hemodialysis and Hemofiltration

Abstract: Trace element concentrations in hair and fingernails and plasma of nondialyzed, hemodialyzed and hemofiltered patients with chronic renal failure and healthy volunteers were measured by atomic and nameless atomic absorption spectrophotometry and neutron activation analysis. Plasma aluminum concentrations in all three groups of patients were higher than in the controls. Aluminum levels in plasma and red blood cells were higher in hemofiltered patients than in dialyzed patients. The aluminum concentrations in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 12 publications
0
9
1
Order By: Relevance
“…It has been reported that the blood concentrations of Pb, Cd, Ni, and Al were higher in the dialysis patients [4,25]. Although elevation of the hair Al concentrations of dialysis patients has been reported in a study performed in the1980s [18] , the hair Al concentrations were not significantly different in hemodialysis patients compared with those in healthy subjects in either the study by Hayashi et al [17] or the present study. This may be due to the fact that much attention has been recently paid to avoid Al contamination in dialysis solutions, since the report of dialysis encephalopathy due to Al in 1976 [26].…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…It has been reported that the blood concentrations of Pb, Cd, Ni, and Al were higher in the dialysis patients [4,25]. Although elevation of the hair Al concentrations of dialysis patients has been reported in a study performed in the1980s [18] , the hair Al concentrations were not significantly different in hemodialysis patients compared with those in healthy subjects in either the study by Hayashi et al [17] or the present study. This may be due to the fact that much attention has been recently paid to avoid Al contamination in dialysis solutions, since the report of dialysis encephalopathy due to Al in 1976 [26].…”
Section: Discussioncontrasting
confidence: 75%
“…Although there was a report of no correlations between the hair and blood concentrations of some elements in dialysis patients [15], the hair may be used as an additional biomarker of elemental status in dialysis patients. However, there have been few studies of trace elements of the hair in dialysis patients [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The modified method allowed the measure ments of V concentrations as low as 0.08 ng/ml in 4-ml serum samples. The Al concentrations in water and the serum were also measured by the fiameless atomic absorption technique (7). Tissue V levels were measured by the nondestructive neutron activation analysis at the Musashi Technical University Research Institute of Nuclear Energy, using the method previously reported (7,8],…”
Section: A Nalyheal Methodsmentioning
confidence: 99%
“…Marumo et al 104 determined nine elements in the plasma, red cells, hair and finger nails of 52 patients with chronic renal failure. Results were reported in detail for calcium, zinc and aluminium.…”
Section: Zincmentioning
confidence: 99%